Analysis of the Impact of Enterprise Employees on Recruitment in Digital Transformation - Zhang, Xinyu (Transactions on Economics, Business and Management Research, 2024)
This article investigates the impact of data-driven transformation on recruitment in multinational corporations. Firstly, the functions and applications of digitalization in recruitment were analyzed. Secondly, the SWOT model was used to analyze data-driven recruitment, including the impact of digitalization on recruitment efficiency, the effects of changes in recruitment methods on specific aspects, and the new impacts on pre job training for new employees. Finally, the impact of digital recruitment was summarized. In addition, based on the summary and analysis of existing literature, it provides reference for the latter to study the impact of digital transformation on recruitment. Through the analysis of SWOT, digital recruitment has greatly improved efficiency and data analysis capabilities, expanded the scope of talent, improved the applicant experience, and helped build the brand image of the enterprise. At the same time, it also has technological dependence and privacy issues. While enjoying the advantages brought by digital recruitment, enterprises also need to take measures to deal with the threats and disadvantages it brings. They also need to seize the opportunities brought by global recruitment to achieve the optimal method for digital recruitment. Digitization has had various impacts on recruitment methods, from candidate screening to recruitment processes, improving the efficiency of digital recruitment, reducing costs, and qualitatively enhancing the experience and recruitment quality of applicants.